Influência da concentração de TeO2 nas propriedades estruturais, térmicas, ópticas e espectroscópicas em vidros cálcio boroteluretos dopados com Yb2O3 - LIMA, Antônia Milena de Oliveira (2016)
This research presents the synthesis and characterization of Yb3+ - doped calcium borotellurite glasses (Yb:CaBTeX). Density, DRX, DTA, specific heat, refractive index, electronic polarizability, optical absorption, luminescence and lifetime measurements were performed to investigate the structural, thermal, optical and spectroscopic properties of Yb:CaBTeX as a function of TeO2 content. The density increased with TeO2 concentration and DRX pattern confirmed the amorphous structure of all samples. The FTIR and Raman spectroscopic indicate the presence of TeO4, TeO3, TeO3+1, BO4 and BO3 units in the network structure. The increase of TeO2 increases the NBO’s and decreases the phonon energy. The DTA analysis shows a decrease of glass transition temperature (Tg) and crystallization temperature (Tx) with increase of TeO2. Also, the addition of TeO2 increases the thermal stability, which presented values above 100 °C for all samples. The specific heat values show a decrease with TeO2 increase, because the bonding enthalpy Te – O is smaller than B – O, consuming less energy to be broken or to vibrate. The refractive index and electronic polarizability values increase with TeO2 content, because Te4+ ions presents larger polarizability than B3+ and Ca2+ ions. The energy band gap and emission intensity of Yb3+ decrease with the increase of TeO2 content, due to the increase of NBO’s and the decrease number of ions per cubic centimeter (N), respectively. There was no variation within the errors, for the radiative lifetime of the Yb:CaBTeX samples. The absorption and emission cross section do not present variation with TeO2 addition and the calculated values are higher than tellurite and phosphate glasses. The analyses showed that Yb3+-doped calcium borotellurite glass feature good combinations of properties, which make them good candidates to be used as photonics devices.